THE USE OF VIDEO AS A SUTURING SKILLS LEARNING RESOURCES IN MEDICAL EDUCATION: A LITERATURE REVIEW - Mega Pandu Arfiyanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Using video in learning showed effective results in practicing clinical skills. Video can also be used to teach the clinical practice and physical examination skills. This literature review paper describes the effectiveness of the use of video as a suturing skills learning resources. We search the journal as a review of the literature through Google Scholar and ScienceDirect by using the term or key word search asfollows "video", "learning resources", "suturing" and "medical education" which, combined with the words “AND” and “OR”. We also restrict the search to journals that published for ten years, between 2005 and 2015. Video as a learning resource should be introduced in the beginning of the lecture. Video is an effective learning resources to teach clinical skills but has several limitations, namely lack ofinteraction between students and students and lecturers as well as the lack of provision of feedback to students. The use of video in education pre-clinical medical students is an effective way to teach students the skills procedure that save time, space and resources used. Keywords : video, learning resources, suturing skill, medical education